Resposta sorológica e proteção fetal contra o vírus da diarréia viral bovina (BVDV) em vacas prenhes imunizadas com uma vacina experimental atenuada - Arenhart, Sandra (2008)
The major goal of bovine viral diarrhea virus (BVDV) vaccines is to confer fetal protection and thus prevent reproductive losses and the production of persistently infected (PI) calves. This dissertation reports the antibody response and fetal protection in pregnant cows conferred by an experimental vaccine containing two attenuated strains of BVDV (BVDV-1 and BVDV-2). Cows previously vaccinated with the experimental vaccine (n=19) and non-vaccinated controls (n=18) were mated and challenged between days 30 and 90 of gestation by intranasal inoculation of four heterologous BVDV-1 and BVDV-2 isolates. The antibody response was evaluated by serum-neutralization tests performed at different intervals after vaccination (days 34, 78 and 138 post-vaccination [pv]). Fetal protection was monitored by ultrassonographic and clinical examination of the dams and fetuses conducted during the rest of gestation; and through virological and serological examination of pre-colostral blood obtained from aborted and/or recently born fetuses/calves. At the day of challenge (day 138 pv), all vaccinated cows had neutralizing antibodies in high titers against BVDV-1 (1.280- >10.240), and with one exception (titer 20), presented moderate to high titers to BVDV-2 (80-1.280). At the end of the experiment only three out of 18 control cows (16.6%) delivered healthy, virus-free calves. Fifteen non-vaccinated cows (83.3%) presented signs of fetal infection and/or had reproductive losses. Seven of these cows (38.8%) delivered virus-positive calves; five were healthy and survived; two were premature or weak and lasted three and 15 days, respectively. The other eight cows (44.4%) aborted between day 30 post-challenge and the parturition; or delivered premature or stillbirth calves. In contrast, 17 out of 19 (89.4%) vaccinated cows delivered virus-free, healthy calves. One vaccinated cow aborted around day 130 post-challenge, yet the aborted fetus could not be examinated for the presence of virus. Another cow delivered a virus-positive calf. These results showed that the experimental vaccine induced adequate antibody titers in most animals and that the immunological response was able to prevent fetal infection and reproductive losses upon challenge with a pool of heterologous BVDV isolates.